Linked Double-Row Equivalent Arthroscopic Rotator Cuff Repair Leads to Significantly Improved Patient Outcomes. Issue 7 (16th July 2020) - Endo, Atsushi; Hoogervorst, Paul; Safranek, Conrad; Sochacki, Kyle R.; Safran, Marc R.; Sherman, Seth L.; Donahue, Joseph
Background: Biomechanical studies have demonstrated that arthroscopic rotator cuff repair using a linked double-row equivalent construct results in significantly higher load to failure compared with conventional transosseous-equivalent constructs. Purpose: To determine the patient-reported outcomes (PROs), reoperation rates, and complication rates after linked double-row equivalent rotator cuff repair for full-thickness rotator cuff tears. Study Design: Case series; Level of evidence, 4. Methods: Consecutive patients who underwent linked double-row equivalent arthroscopic rotator cuff repair with minimum 2-year follow-up were included. The primary outcome was the American Shoulder and Elbow Surgeons (ASES) score at final follow-up. Secondary outcomes included the Simple Shoulder Test (SST), shortened Disabilities of the Arm, Shoulder and Hand (QuickDASH) questionnaire, visual analog scale (VAS), reoperations, and complications. Clinical relevance was defined by the minimally clinically important difference (MCID). Comparisons on an individual level that exceeded MCID (individual-level scores) were deemed clinically relevant. Comparisons between preoperative and postoperative scores were completed using the Student t test. All P values were reported with significance set at P < .05. Results: A total of 42 shoulders in 41 consecutive patients were included in this study (21 male patients [51.2%]; mean age, 64.5 ± 11.9 years; mean follow-up, 29.7 ± 4.5 months). All patients (100%) completed the minimum 2-year follow-up. The rotator cuff tear measured on average 15.2 ± 8.9 mm in the coronal plane and 14.6 ± 9.8 mm in the sagittal plane. The ASES score improved significantly from 35.5 ± 18.2 preoperatively to 93.4 ± 10.6 postoperatively ( P < .001). The QuickDASH ( P < .001), SST ( P < .001), and VAS ( P < .001) scores also significantly improved after surgery. All patients (42/42 shoulders; 100%) achieved clinically relevant improvement (met or exceeded MCID) on ASES and SST scores postoperatively. There were no postoperative complications (0.0%) or reoperations (0.0%) at final follow-up. Conclusion: Arthroscopic repair of full-thickness rotator cuff tears with the linked double-row equivalent construct results in statistically significant and clinically relevant improvements in PRO scores with low complication rates (0.0%) and reoperation rates (0.0%) at short-term follow-up.